2006
DOI: 10.1111/j.1600-0579.2006.00415.x
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes of dental and medical students in their first and final years of undergraduate study to oral health behaviour

Abstract: There were significant differences in oral health attitudes and behaviours in dental students between entrance to University and the final year of their study. The same was not found to be true for medical students.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
33
0
6

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(47 citation statements)
references
References 16 publications
(17 reference statements)
8
33
0
6
Order By: Relevance
“…According to previous studies, dental students have better oral hygiene (18) and better knowledge on tooth bleaching, which can be explained by education they receive during the study of dental medicine and by their attitude towards oral health (18,20,21). Šimat et al (18) reported that students from the School of Dental Medicine have better oral hygiene habits than students from other faculties, while DMFT index is associated with a lack of prevention at a young age, regardless of the group of subjects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to previous studies, dental students have better oral hygiene (18) and better knowledge on tooth bleaching, which can be explained by education they receive during the study of dental medicine and by their attitude towards oral health (18,20,21). Šimat et al (18) reported that students from the School of Dental Medicine have better oral hygiene habits than students from other faculties, while DMFT index is associated with a lack of prevention at a young age, regardless of the group of subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Studenti dentalne medicine, očekivano, više vode brigu o oralnoj higijeni (18) i pokazali su bolje znanje o postupku izbjeljivanja zuba, što je i razumljivo s obzirom na to da tijekom studija proširuju znanje i tako stvaraju odnos prema oralnome zdravlju (18,20,21). Na temelju istraživanja Ši-mata i suradnika provedenom među studentima Sveučilišta u Zagrebu, može se zaključiti da je dentalna higijena studenata dentalne medicine bolja negoli onih s ostalih fakulteta, a vrijednosti KEP indeksa upućuju na nedostatak prevencije u mlađoj dobi, neovisno o skupini ispitanika (18).…”
Section: Raspravaunclassified
“…Such studies have primarily been conducted among dental and medical students (Kawamura et al, 2005;Rong et al, 2006;Peker and Toraman Alkurt, 2009;Peker et al, 2010;Yildiz and Dogan, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…19 Thus, it can provide the possibility of comparison among various countries, and to assess cross-cultural differences. One study comparing dental and medical students by HU-DBI questionnaire showed that during undergraduate education, medical students' attitudes did not change while that of dental students was changed 12 .…”
Section: Introductionmentioning
confidence: 99%
“…Oral health attitudes and behaviour among medical and dental students in Tehran, Iran HU-DBI questionnaire has been administered in many countries such as UK, 9 USA, 10 South Korea, 11 China, 12 Yemen, 13 Greece, 14 Romania, 15 Turkey, 16 India 17,18 and Jordan. 19 Thus, it can provide the possibility of comparison among various countries, and to assess cross-cultural differences.…”
Section: Introductionmentioning
confidence: 99%